2022
DOI: 10.26434/chemrxiv-2022-lh6s3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exciton states of azobenzene aggregates: A first-principles study

Abstract: Interaction between azobenzene-containing molecules in supramolecular structures or self-assembled monolayers (SAMs) results in the formation of molecular exciton states. These states determine photophysical and photochemical processes in such assemblies. Here, using first-principles quantum chemical calculations, we study optical spectra and exciton delocalization of the exciton states in model clusters of azobenzene molecules. Specifically, we consider one-dimensional linear chains and two-dimensional SAM-li… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 70 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…We note that in the simple exciton model (considering an H-aggregate composed of identical monomer geometries with the same non-zero transition dipole moment), a larger enhancement should occur for a smaller separation distance owing to a larger exciton splitting. 25 As discussed previously for the dimeric models, 57 the trend in absorbance observed for the nπ * band upon aggregation is determined by the extent of deviation of the monomers forming an aggregate from the equilibrium, planar C 2h geometry.…”
Section: Absorption Spectrum and Initial Exciton Localizationmentioning
confidence: 75%
See 1 more Smart Citation
“…We note that in the simple exciton model (considering an H-aggregate composed of identical monomer geometries with the same non-zero transition dipole moment), a larger enhancement should occur for a smaller separation distance owing to a larger exciton splitting. 25 As discussed previously for the dimeric models, 57 the trend in absorbance observed for the nπ * band upon aggregation is determined by the extent of deviation of the monomers forming an aggregate from the equilibrium, planar C 2h geometry.…”
Section: Absorption Spectrum and Initial Exciton Localizationmentioning
confidence: 75%
“…14 Moreover, several studies have reported first-principles calculations of exciton states of azobenzene aggregates and SAMs. [20][21][22][23][24][25] However, these studies address exciton states for fixed nuclear configurations of the aggregates. To go beyond this single-geometry picture, it is necessary to account for ground-state conformational (geometrical) disorder (induced by thermal fluctuations) and excited-state dynamical effects.…”
Section: Introductionmentioning
confidence: 99%
“…7,22 Furthermore, quantum chemical calculations on azobenzene dimers and larger aggregates yielded sizable exciton splittings (of several hundreds meV) for the bright, ππ * states, suggesting rapid excitation energy transfer between monomers. [23][24][25][26] The simplest theoretical modelling of the steric effects on photodynamics of a photoswitch requires a quantum mechanical (QM) description of a single chromophore, whereas an environment can be described with classical molecular mechanics (MM). This approach has been applied to reveal the role of steric hindrance for azobenzene isomerization in various systems, such as azobenzene (or its derivatives) on a surface, 27,28 in a SAM, 29 attached to RNA, 30 in a micelle, 13 and in a lipid membrane.…”
Section: Introductionmentioning
confidence: 99%